FRI0116 SUBCUTANEOUS TOCILIZUMAB IN MONOTHERAPY OR IN COMBINATION WITH CSDMARD IN PATIENTS WITH MODERATE TO SEVERE RHEUMATOID ARTHRITIS: OBSERVATIONAL STUDY TO DESCRIBE REAL-WORLD DRUG RETENTION RATE AT 12 MONTHS. (June 2019) - Saraux, Alain; Barnetche, Thomas; Baudens, Guy; Idier, Isabelle; Delaporte, Flore; Hilliquin, Pascal
Abstract : Background: Rate of discontinuation and drug survival of biologic therapies in rheumatoid arthritis (RA) is about 60-70% in real life at one year 1 . In France, all biologics 1st prescription and yearly renewal are reimbursed, restricted to hospital rheumatologists, with renewal and monitoring done by both office-based or hospital rheumatologists. Objectives: To evaluate the 12-month drug retention rate, efficacy and tolerance of tocilizumab (TCZ) subcutaneous (sc) in RA patients (pts). Study design: prospective, multicentre, observational 18-month study. Pts : moderate to severe active RA requiring TCZ sc as prescribed in real life. Primary endpoin t: drug retention rate of TCZ sc at 12 months in pts followed by hospital- and office-based rheumatologists, estimated using Kaplan-Meier method. Secondary endpoints : pts' characteristics, concomitant treatments, adherence to TCZ sc using the Compliance Questionnaire for Rheumatology (CQR5), efficacy, safety of TCZ sc and QoL using EQ-5D. Statistical analysis : pts with ≥1 TCZ injection were analyzed for safety. Pts fulfilling inclusion and non-inclusion criteria were analyzed for efficacy. Results: 291 pts were recruited, 286 were analyzed for safety and 285 for efficacy. Baseline: mean age 56.2±12.5 years, females: 74.7%, at least 1 co-morbidity: 71.9%, mean RA duration 9.4±9.0 years, RF and/or ACPA: 83.4%, erosive RA: 60.8%, mean DAS28-ESR 4.77±1.21. Past RA treatments were csDMARDs in 94.4%, biologics in 62.8%. EQ-5D Health state was 0.53±0.19. TCZ Mono (i.e. without csDMARD) was initiated in 124 (43.5%), TCZ Combo in 158 (55.4%) pts, 84.8% of whom received MTX (17.3±4.4mg/w). Glucocorticoids (GCs) were used in 48.9% of the pts (9.99±9.36mg/day). Follow up: 161 and 148 pts completed M12 and M18 visits. 138 pts withdrew including AE 61, lack of efficacy 37, pts/doctor wish 24. At M12, drug retention rate was 63.6%: 62.6% in Mono, 64.3% in Combo (Fig.1 ); with similar results for pts ≤/> 65 years old and for pts ≤/> 30Kg/m 2 . 5 Mono pts had ongoing csDMARD and 9 Combo pts had no csDMARD. 15.3% and 19.0% used GCs, 16.19±11.95mg/d in the Mono and 17.36±16.65mg/d in the Combo groups. Total number of TCZ injections was 36.74±25.84 done by pt in 54.0%. Mean time between 2 TCZ injections was 8.48±10.70 days. Adherence to TCZ was high in 86.5% of the 89 pts who completed CQR5 at month 12. It was 52.9% for the 121 pts who completed pts diary over the month 12-month 18 period. Mean DAS28 in all, Mono and Combo were 1.91±1.11, 1.66±1.02, 2.12±1.14 respectively. EULAR good and moderate responses were respectively 61.3 and 7.7% in all: 67.2 and 4.9% in Mono; 56.8 and 9.9% in Combo pts. EQ-5D improved in all domains with a change from baseline of 0.11±0.29. 234 (81.8%) pts had at least 1 adverse event (AE), 46 (16.1%) had at least 1 serious AE including 11 infections, 2 GI perforations and 2 deaths (pneumopathy and bronchial carcinoma). Conclusion: At 12 months, drug retention rate was 63.6% in patients receiving TCZ sc in real life, with no difference between Mono and Combo groups. EULAR good/moderate response was 69.0%. QoL improved in all EQ-5D domains. No new safety signal occurred. Reference: [1] Souto A, et al. Rate of discontinuation and drug survival of biologic therapies in rheumatoid arthritis. Rheumatology (Oxford) 2016 Mar;55(3):523-34. Disclosure of Interests: Alain Saraux Consultant for: Roche SAS, Speakers bureau: Chugai Pharma France, Thomas Barnetche Consultant for: Roche SAS, Guy Baudens Grant/research support from: Financial Grant from NordicPharma, Consultant for: Roche SAS, Isabelle Idier Employee of: ChugaiPharma france, Flore Delaporte Employee of: Roche SAS, Pascal Hilliquin Consultant for: Roche SAS